The role of benefit perception and customer satisfaction toward intention to continue moderated purchases experience preference satisfaction (study on Samsung consumers in Solo Raya) - Novita Dewi, Septiana; Laksmi Riani, Asri; Harsono, Mugi; Ikhwan Setiawan, Ahmad (International Journal of Engineering and Technology, 2019)
Indonesian consumer behavior patterns have used the Internet trend, making them become information sharing and socialization to maintain the existence of the company. The pattern of personality, consumers, has also made changes in its customer organizations (Jayachandran et al., 2004). This research was first used as a result of research to find out the results of research and to reveal customer satisfaction with purchase intentions. The purpose of this study was to determine the effect, customer satisfaction on purchase intentions with the center of attention as moderating. The population in this study are consumers who choose to use Samsung Brand Mobile in Solo Raya Region. The sample studied was 180 respondents. Sampling was 180 respondents by multiplying 5 to 10 the number of parameters estimated (Ferdinand, 2014). The analytical method used in this study Structural Equation Modelling (SEM). Perceptions of negative and insignificant effects on purchase intention. Customer satisfaction is positive and significant towards purchase intention. The strength of the style of style modifies between customer satisfaction and repurchase intention. Â Â